Deeper diversity exploration: New Typhlotanaidae (Crustacea: Tanaidacea) from the Kuril-Kamchatka Trench area - Gellert, Marta; Palero, Ferran; Błażewicz, Magdalena (Frontiers in Marine Science, 2022)
Typhlotanaidae Sieg, 1984, is one of the most diverse Tanaidacea families from deep-sea waters. Its diversity is underestimated, and evolutionary relationships within the family remain mostly unknown. Deep-sea typhlotanaids collected from 23 sites across the Kuril-Kamchatka Trench and nearby waters were studied using an integrative taxonomy approach, combining morphological and genetic data (i.e., the mitochondrial subunit I of the cytochrome oxidase (COI) and the 18S rDNA nuclear gene). One new species of Typhlamia and two new species belonging to two new genera are described, significantly increasing the known diversity of typhlotanaids from the NW Pacific. The molecular phylogeny obtained, despite being preliminary results, was congruent with morphological data and supports the monophyly of different groups such as the ‘short-bodied’ forms (represented by Ty. cornutus and Ty. eximius) or the ‘collar’ forms (e.g., Ty. variabilis and Torquella). Molecular data confirm the non-monophyly of Typhlotanais species. Finally, the new typhlotanaid taxa seem to have distinct bathymetric distribution and ecological requirements, but further data on environmental factors and species abundances are still needed.